The Italian Angevins: Naples and Beyond, 1266–1343. - Gilbert, Jane; Keen, Catherine; Williams, Ella (Italian Studies, 2017)
An introduction is provided to the special issue on the theme of the house of the Angevins in the region of Naples, Italy from 1266 through 1343 with topics, including Angevin cultural history, Angevin social networks and the Angevin court.